PEMETAAN POTENSI AIR TANAH (GROUNDWATER) BERDASARKAN METODE VERTICAL ELECTRICAL RESISTIVITY (VES) DI DESA JABUNG, KABUPATEN MALANG - Puspita, Mayang Bunga; Aprilia, Faridha (EduFisika: Jurnal Pendidikan Fisika, 2022)
Jabung Village, located in Jabung District, Malang Regency, has various groundwater potentials. The study using the Vertical Electrical Sounding (VES) geoelectric method was carried out in several hamlets in Jabung Village with water shortages to map the groundwater potential in these hamlets. VES measurements were carried out in Boro Lor Hamlet, Gunung Kunci Hamlet, Umpak Hamlet, and Mindi Hamlet, with 1 reference point measured next to a drilled well belonging to the Regional Government. The results of VES analysis in 4 hamlets show that the aquifer layer is a sandstone with a resistivity of 25.8-41.7 m. The thickness of the aquifer varies from 4.6 meters to 30.1 meters. The depth of the aquifer also varies from a depth of 40.6 meters to a depth of 68.6 meters.